Feminist Collections, v.21, no.1 (fall 1999) - (:unkn) unknown (My University, 1999)
Subtitle: A Quarterly of Women's Studies Resources. 50p.
FROM THE EDITORS. BOOK REVIEWS: Voices on War and Peace, by Sheila Tobias. Engendering War, by Francine D'Amico. Chicanas in the U.S.: Multiple Identities, by Dionne Espinoza. Taking Sportswomen Seriously: Seven Novels for Adults, by Joli Sandoz. FEMINIST VISIONS: Gender, Race, and Class Issues on Film, by Deb Hoskins. FEMINISM AND LITERACY FOR WOMEN: POLITICS AND RESOURCES: By Mev Miller. WORLD WIDE WEB REVIEW: Women and Women's Topics on the Internet: What's the Situation in Germany Today?, by Carolina Brauckmann and Helga Dickel. COMPUTER TALK: Compiled by Linda Shult. NEW REFERENCE WORKS IN WOMEN'S STUDIES: Reviewed by Phyllis Holman Weisbard and others. PERIODICAL NOTES: Compiled by Linda Shult. ITEMS OF NOTE: Compiled by Jennifer Kitchak. BOOKS RECENTLY REVIEWED.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews; War and Peace; Chicanas; Novels About Sportswomen; Literacy; German Women